基于原型范畴理论的“斋”在国际中文教育中的应用研究 A Study on the Application of the "Zhai"Concept inTCFL Based on Prototype Category Theory - 王神黎, Julianti; Hao, Zhang (Jurnal Asosiasi Program Studi Mandarin Indonesia (Jurnal APSMI), 2025)
摘要：本文运用原型范畴理论对“斋”字进行深入分析，旨在探索“斋”字原型语义的特征及其语义范畴体系，并从中将关于“斋”字的研究成果融入国际中文教育的文化教学课程和词汇教学中。研究成果显示，已明确“斋”的原型特征包括身心的净化、虔诚的表达以及特定的仪式。基于这些原型特征，“斋”形成了一个由典型范畴成员和边缘范畴成员构成的复杂语义范畴体系。典型范畴成员紧密围绕祭祀和宗教仪式，充分展现了“斋”的原型特征。而边缘范畴成员则是在语义演变过程中基于原型特征的语义延伸，涵盖了场地建筑、饮食、职称头衔以及别名等多个领域。这一语义范畴体系的构建，为我们理解“斋”在不同语境下的语义变化提供了清晰的框架。因此，我们把“斋”的研究成果融入国际中文教育的应用。在文化教学方面，可以通过开设专题课程、举办模拟祭祀和斋戒活动、制作斋菜以及开展跨文化比较等实践活动。而在词汇教学方面，以原型范畴理论为基础，通过有针对性的读写训练，可以剖析词汇的语义关系，构建起词汇网络。关键词：国际中文教育，斋，原型范畴理论，历史演变Abstract:The prototype characteristics of "Zhai" have been clearly defined, including the purification of the body and mind, the expression of piety, and specific rituals. Based on these prototype characteristics, "Zhai" has formed a complex semantic category system composed of typical and marginal category members. The typical category members closely revolve around sacrificial and religious rituals, fully demonstrating the prototype characteristics of "Zhai". The marginal category members are semantic extensions based on the prototype characteristics during semantic evolution, covering multiple fields such as venue architecture, diet, professional titles, and aliases. The construction of this semantic category system provides a clear framework for us to understand the semantic changes of "Zhai" in different contexts. Therefore, we integrate the research results of "Zhai" into the application of international Chinese education. In cultural teaching, practical activities such as offering special courses, holding simulated sacrificial and fasting activities, preparing vegetarian dishes, and carrying out cross-cultural comparisons can be carried out. In terms of vocabulary teaching, based on the prototype category theory, through targeted reading and writing training, the semantic relationships of words can be analyzed, and a vocabulary network can be constructed.Keywords:International Chinese Language Education, Zhai (ritual purification), Prototype Theory, historical evolution